v.22 - "Keynes, John Maynard" (New Delhi, 2013)
Between the outbreak of war in 1939 and his death in 1946 Keynes was closely involved in the management of Britain's war economy and the planning of the post-war world. This volume, the first of several dealing with this period, focuses on two aspects of his activities during the war: his efforts as a private citizen to influence opinion of the tasks ahead prior to July 1940, and his contributions within the Treasury to Britain's internal financial management thereafter. It contains the correspondence and memoranda surrounding How to Pay for the War, perhaps his most successful essay in persuasion; the 1941 Budget, the first explicitly Keynesian Budget in Britain; the development of the associated national income estimates; and his later attempts to influence other areas of financial policy. This is a necessary companion to How to Pay for the War, which appears in Volume 9 of this series.
Keywords: Keynesianism